Learning to â€˜Parentingâ€™: Peer-to-Peer Educational Actions in the Italian Associations of Adoptive Families - Silvio, Rossana Di (Richtmann Publishing, 2012)
We hardly associate parenthood to a state that must be learned or taught according to classical educative models,rather we think that it is an embedded condition arising â€œnaturallyâ€ when we become parents. Nowadays, however, with the riseof the so-called â€œpsyâ€ sciences, the certainty and solidity of a noun - parenthood â€“ has been progressively replaced by theproceedings of a verb - parenting. The idea of parenting as a process of learning (emotional, cognitive and behavioral) finds itsmost concrete expression in the construction of the adoptive parenthood. Based on a two yearsâ€™ ethnographic research, mypaper aims at highlighting the training action carried out by adoptive associations towards the infertile couples who have decidedto adopt. In a society that is still deeply family-based, such as the Italian one, where kinship ties are grounded in the hegemonicaction of the blood paradigm, a widespread cultural belief claims that a failed bio-reproduction deprives the couples of thatnatural embedded knowledge necessary to be good parents. So, if the rule allows to legitimize the shift from a legal status (thecouple) to another (the family), the associations of adoptive families are authorized by the State to carry out an intensiveeducative action so that the prospective parents can better learn all the qualities, behaviors, responsibilities and emotions typicalof good adoptive parents, according to the â€œnaturalâ€ model of the biological parenting.